PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2009-2011) - Yossita Kartikasari P; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to empirically examine the effect of intellectual capital on the financial performance of banking. Intellectual capital measurement model using Pulic models, which in the aggregate - Value Added Intellectual Coefficient (VAIC™) with the major components of a basic resource companies - physical capital (VACA), human capital (VAHU), and structural capital (STVA) and three elements financial performance of the banking company which consists of Return on Assets (ROA), Capital Adequacy Ratio (CAR), and the loan to deposit ratio (LDR).The data used is the banking companies listed in Indonesia Stock Exchange (IDX) 2009-2011. This empirical study using PLS (Partial Least Squares) as an analysis of the relationship between intellectual capital (VAIC™) on the financial performance of banking.The findings show that: (1) intellectual capital (VAIC™) significantly affects the financial performance of the banking company, (2) intellectual capital insignificant effect on the financial performance of the banking companies of the future, and, (3) the rate of growth of intellectual capital (ROGIC) insignificant effect on the future financial performance of banking.